A study of the cognitive and psychological attributes of language comprehension during cultural exchange among athletes - Xiaohua Shi; Yuekun Shao (Revista de Psicología del Deporte (Journal of Sport Psychology), 2023)
This study reports on the cognitive and psychological attributes of language comprehension during cultural exchange among athletes (N = 20) from the United States, Great Britain, and Brazil. The research examined the linguistic significance of American English in a global marketplace, with particular attention to cross-cultural communication among those who speak U.S. English natively but must succeed in internationally competitive contexts. The major results demonstrated that while speaking their mother tongue, individuals were typically more confident and less likely to feel ashamed than when using their individual second language (English). Athletes were also shown to have no trouble distinguishing between languages, as they were able to recognise certain terms in both Spanish and Portuguese despite not being competent in either language. The results were understood to mean that, despite not being competent in a second language, athletes kept their capacity to think and converse about the world in an English-language framework.